2015
DOI: 10.6061/clinics/2015(02)06
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in medication adherence and self-management of diabetes with a clinical pharmacy program: a randomized controlled trial in patients with type 2 diabetes undergoing insulin therapy at a teaching hospital

Abstract: OBJECTIVE:To evaluate the impact of a clinical pharmacy program on health outcomes in patients with type 2 diabetes undergoing insulin therapy at a teaching hospital in Brazil.METHOD:A randomized controlled trial with a 6-month follow-up period was performed in 70 adults, aged 45 years or older, with type 2 diabetes who were taking insulin and who had an HbA1c level ≥8%. Patients in the control group (CG) (n = 36) received standard care, patients in the intervention group (IG) (n = 34) received an individualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(136 citation statements)
references
References 33 publications
(43 reference statements)
9
124
1
2
Order By: Relevance
“…The pharmacist continuous follow up and advice for their glycemic control in the intervention group can develop a trustable close professional relationship between the pharmacist and patients as a part of the educational program might has contributed to a better glycemic control in this study. These findings are similar to those of other studies conducted in other countries which show that the pharmacist led patient education and medication counseling was effective in improving medication adherence and glycemic levels in patients with type 2 diabetes mellitus [17][18][19][20][21][22][23][24][25][26].…”
Section: Outcome Of Glycemic Levelssupporting
confidence: 82%
“…The pharmacist continuous follow up and advice for their glycemic control in the intervention group can develop a trustable close professional relationship between the pharmacist and patients as a part of the educational program might has contributed to a better glycemic control in this study. These findings are similar to those of other studies conducted in other countries which show that the pharmacist led patient education and medication counseling was effective in improving medication adherence and glycemic levels in patients with type 2 diabetes mellitus [17][18][19][20][21][22][23][24][25][26].…”
Section: Outcome Of Glycemic Levelssupporting
confidence: 82%
“…Among the studies included in this review, n = 3 were cluster-randomized controlled trials, (Armour et al, 2004; Krass et al, 2007; Mehuys et al, 2011) whereas rest of the studies, n = 40 were parallel randomized controlled trials (Sarkadi and Rosenqvist, 2004; Clifford et al, 2005; Hayward et al, 2005; Odegard et al, 2005; Rothman et al, 2005; Suppapitiporn et al, 2005; Taylor et al, 2005; Fornos et al, 2006; Scott et al, 2006; Ko et al, 2007; Al Mazroui et al, 2009; Doucette et al, 2009; Jameson and Baty, 2010; Kang et al, 2010; Taveira et al, 2010; Cohen et al, 2011; Farsaei et al, 2011; Sriram et al, 2011; Ali et al, 2012; Chan et al, 2012; Jacobs et al, 2012; Jarab et al, 2012; Mahwi and Obied, 2013; Mourão et al, 2013; Samtia et al, 2013; Castejón et al, 2014; Chung et al, 2014; Ahmad et al, 2015; Cani et al, 2015; Chow et al, 2015; Jahangard-Rafsanjani et al, 2015; Wishah et al, 2015; Butt et al, 2016; Chen et al, 2016; Lim et al, 2016; Nascimentoa et al, 2016; Tourkmani et al, 2016; Korcegez et al, 2017; Shao et al, 2017; Siaw et al, 2017). Most of the included studies ( n = 20) were conducted in Asia (Suppapitiporn et al, 2005; Ko et al, 2007; Kang et al, 2010; Farsaei et al, 2011; Sriram et al, 2011; Chan et al, 2012; Jarab et al, 2012; Mahwi and Obied, 2013; Samtia et al, 2013; Chung et al, 2014; Chow et al, 2015; Jahangard-Rafsanjani et al, 2015; Wishah et al, 2015; Butt et al, 2016; Chen et al, 2016; Lim et al, 2016; Tourkmani et al, 2016; Shao et al, 2017; Siaw et al, 2017), followed by North America ( n = 11) (Hayward et al, 2005; Odegard et al, 2005; Rothman et al, 2005; Scott et al, 2006; Doucette et al, …”
Section: Resultsmentioning
confidence: 99%
“…Most of the included studies ( n = 20) were conducted in Asia (Suppapitiporn et al, 2005; Ko et al, 2007; Kang et al, 2010; Farsaei et al, 2011; Sriram et al, 2011; Chan et al, 2012; Jarab et al, 2012; Mahwi and Obied, 2013; Samtia et al, 2013; Chung et al, 2014; Chow et al, 2015; Jahangard-Rafsanjani et al, 2015; Wishah et al, 2015; Butt et al, 2016; Chen et al, 2016; Lim et al, 2016; Tourkmani et al, 2016; Shao et al, 2017; Siaw et al, 2017), followed by North America ( n = 11) (Hayward et al, 2005; Odegard et al, 2005; Rothman et al, 2005; Scott et al, 2006; Doucette et al, 2009; Jameson and Baty, 2010; Taveira et al, 2010; Cohen et al, 2011; Jacobs et al, 2012; Castejón et al, 2014; Korcegez et al, 2017), Europe ( n = 5) (Sarkadi and Rosenqvist, 2004; Fornos et al, 2006; Mehuys et al, 2011; Ali et al, 2012; Nascimentoa et al, 2016), Australia ( n = 4) (Armour et al, 2004; Clifford et al, 2005; Taylor et al, 2005; Krass et al, 2007), South America ( n = 2) (Mourão et al, 2013; Cani et al, 2015), and Africa ( n = 1) (Ahmad et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…It has been indicated in this study that 89 (32.4%) of the patients are not exercising. Compared to a study conducted in Finland indicated 10% T2DM took no exercise at all [34], that of this study the findings are high, that is 32.4% [35]. In this study it was found that T2DM patients who don't exercise every day for more than 30 minutes a day with (pvalue 0.001) (AOR=3.12, 95% CI: 1.607-6.116) are three times more likely to be non-adherent, similar to a cross-sectional study conducted in the southeastern region of Brazil, It was reported that exercise (p=0.006) were significantly associated with the chance of patients, with non-adherence to exercise is almost twice more likely for nonadherence to their medications [36,41].…”
Section: Discussionmentioning
confidence: 99%